Dampak Bullying terhadap Perkembangan Psikologi Anak: Perspektif Q.S. Al-Hujurat Ayat 11 dalam Pembentukan Karakter Siswa Pendidikan Dasar - Mukmin; Muslimin; Muhammad Aminullah; Nurlaila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the impact of bullying on the psychological development of children at the primary education level, with the perspective of Q.S. Al-Hujurat verse 11. Bullying can harm children's psychological development in emotional, social, and character-building aspects. The verse teaches the importance of mutual respect and avoiding behavior that degrades others, which is relevant in addressing bullying in the school environment. The research method used is qualitative, with a literature review approach and text analysis. Data was gathered through a review of literature related to bullying and the interpretation of Q.S. Al-Hujurat verse 11. This study also involves observations regarding bullying behavior in primary school settings. The results indicate that bullying can lead to psychological disturbances in children, such as anxiety, depression, low self-esteem, and difficulties in building social relationships. The perspective of Q.S. Al-Hujurat verse 11 offers social ethical values that emphasize the importance of maintaining harmony among individuals and avoiding behaviors that can harm social relationships. The conclusion of this study is that character education based on Quranic values, particularly those contained in Q.S. Al-Hujurat verse 11, can serve as a strong foundation for preventing and addressing bullying in primary schools. Efforts to prevent bullying through the development of character that emphasizes respect and mutual appreciation should be implemented in primary education to protect the psychological development of children.